Evaluasi Program Outbound di TK Menggunakan Model Context, Input, Process, Product (CIPP) - Ryan Hasanudin; Wulan Siti Hajar (UIN Raden Mas Said Surakarta, 2020)
The problem in this research is that there is no evaluation of the outbound program. This study aims to evaluate the Outound Program at TK Pilang 01 for the 2019/2020 academic year. This research uses mixed methods, which is a combination of qualitative and quantitative research using a descriptive approach. This research was conducted from January to April 2020. The subjects in this study were students and the informants were teachers and school principals. Methods of data collection using observation, interviews and documentation and questionnaires. The data analysis technique used interactive analysis, while the questionnaire was analyzed using percentage (percentile) analysis. The conclusion of the context evaluation is that the Outbound program objectives get a score of 80%. Evaluation of the input in this study in the form of children's kinesthetic intelligence abilities and available funding sources obtained a score of 80%. Process Evaluation obtained a score of 75%. Product Evaluation earned a score of 85%. Based on the results of the evaluation, the recommendation given is to continue the program, because the implementation of the program has gone according to expectations and has provided useful results.